India's economy in the 21st century - Kapila, Raj (Ed.); Kapila, Uma (Ed.) (Delhi Academic Foundation, 2001)
India's economy in the 21st century discuss the process of growth in Indian economy since 1950 analysing the constraints on growth the emenging economic challenges the economic reforms and policy agenda for the future.This book cover the monetary policy o
Keywords: Economics-India; Economic development; Economic Policy; Agriculture-India